Factors Related to The Utilization of The Integrated Development Posts of Non-Convenient Diseases in The Pandemic Era in The Work Area of Sekolaq Health Centre in 2022 - Bengan, Fallentina; Nulhakim, Lukman; Tini, Tini (Rifa'Institute, 2022)
Introduction: Integrated Development Post of Non-Convenient Diseases is an activity for early detection and monitoring of risk factors for Non-Communicable Diseases that is oriented towards promotive and preventive efforts, from data on 593 patient visits during the pandemic era at the Sekolaq Darat District Health Centre, more than 92% were included in the Non-Communicable Diseases category and only 39% of sufferers of Non-Communicable Diseases attended the Integrated Non-Communicable Diseases Guidance Post. Objective: This study aims to describe and examine the relationship between variables, namely factors related to the use of Non-communicable Disease Integrated Development Posts in the Pandemic Era. Methods: The research design is a descriptive correlation with a cross-sectional approach. The statistical test used is nonparametric with Chi-Square. Results and Discussion: The relationship between knowledge, support from health workers, family support, and attitudes with the utilization of Integrated Development Post of Non-Convenient Diseases obtained p-value = 0.00<0.05 and the relationship between work and utilization of Integrated Development Post of Non-Convenient Diseases obtained p-value = 0.09>0.05. Conclusion: Knowledge, support from health workers, family support and attitudes are factors related to the utilization of the Non-Communicable Diseases Integrated Development Post